Acoustic Emission for the detection of shaft-to-seal rubbing in large power generation turbines - Leahy, Mark J.; Mba, David; Cooper, P.; Montgomery, A.; Owen, D. (Trans Tech Publications, 2006)
An empirical investigation is undertaken in order to assess the potential of the AE technique for the detection of seal-to-rotor rubbing in steam turbines. Rubbing was induced at various axial locations along a 4 ½ tonne test rotor, rotating at 3000 rpm and supported by 7” (178mm) journal bearings. This paper examines the capabilities of bearing mounted AE transducers for the detection of seal-torotor rubbi
Proceedings of the 27th European Conference on Acoustic Emission Testing (EWGAE 2006), 20-22 September 2006, Cardiff, Wales, UK
Keywords: Acoustic emissions; condition monitoring; seal rubbing